Evaluation of internal pore structure of porous asphalt concrete based on laboratory testing and discrete-element modeling. (1st March 2021) - Zhu, Junqing; Ma, Tao; Lin, Zihao; Xu, Jian; Qiu, Xiaohua
Highlights: A relative indicator of percent effective voids was proposed to evaluate void structure of PAC. The indicator of t/NMAS shows better correlation with percent effective voids than NMAS. Interfering size aggregate and asphalt binder content have negative impact on percent effective voids. Higher interconnected void content creates more open channel for water to flow and thus increases permeability. Abstract: Permeable pavement constructed with porous asphalt concrete has been more widely used due to its environmental significance (reducing stormwater runoff, recuing traffic noise) and traffic safety advantages. Research regarding permeability and pore structural characteristics of PAC is one of the front topics and yet gaps of knowledge still exist in this area. Pore structure is the primary factor in permeability of porous asphalt concrete (PAC) pavement. The composition and distribution of different pore components of PAC and their impact on permeability and influence factors are worth exploring. This paper evaluates pore structure of PAC using both laboratory tests and discrete element modeling (DEM) simulations. PAC specimens with varying nominal maximum aggregate size (NMAS) and varying gradations were prepared and tested in the laboratory to obtain their total void contents and effective void contents. Permeability tests were conducted to evaluate relationship between pore structure and permeability. A relative indicator of percent effective voids was proposed to evaluate void structure of PAC and was proven to be better indicator than absolute void contents. Laboratory test results revealed that t/NMAS, which is lift thickness divided by NMAS shows better correlation with percent effective voids than NMAS. Interfering size (D2.36) aggregate has a negative impact on percent effective voids and the impact is more significant on smaller size mixes. Discrete-element method (DEM) was utilized to further explore the micro-meso structural characteristics of pore structure of PAC. It was revealed that higher interconnected void content creates more open channel for water to flow and is essentially the cause of increasing permeability. Contributions of interconnected voids in terms of creating void volume is significantly higher than dead-end voids and isolated voids.